2016
DOI: 10.1371/journal.pone.0149258
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic, Phenotypic and Clinical Validation of GeneXpert in Extra-Pulmonary and Pulmonary Tuberculosis in India

Abstract: BackgroundNewer molecular diagnostics have brought paradigm shift in early diagnosis of tuberculosis [TB]. WHO recommended use of GeneXpert MTB/RIF [Xpert] for Extra-pulmonary [EP] TB; critics have since questioned its efficiency.MethodsThe present study was designed to assess the performance of GeneXpert in 761 extra-pulmonary and 384 pulmonary specimens from patients clinically suspected of TB and compare with Phenotypic, Genotypic and Composite reference standards [CRS].ResultsComparison of GeneXpert result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 32 publications
2
38
2
6
Order By: Relevance
“…Despite a few misses, the assay offers major boost to early diagnosis of TB and MDR-TB, in difficult to diagnose pauci-bacillary TB. [15] The Xpert MTB/RIF assay demonstrated a high capability to detect MTBC DNA in AFB microscopy-negative samples of pulmonary and extrapulmonary origin. With the exception of a specimen harbouring a mixed MTBC population, the assay correctly retrieved information from the rpoB hot spot region regarding RMP resistance.…”
Section: R E S U L T Smentioning
confidence: 99%
“…Despite a few misses, the assay offers major boost to early diagnosis of TB and MDR-TB, in difficult to diagnose pauci-bacillary TB. [15] The Xpert MTB/RIF assay demonstrated a high capability to detect MTBC DNA in AFB microscopy-negative samples of pulmonary and extrapulmonary origin. With the exception of a specimen harbouring a mixed MTBC population, the assay correctly retrieved information from the rpoB hot spot region regarding RMP resistance.…”
Section: R E S U L T Smentioning
confidence: 99%
“…Thus, the advantage of the Gene Xpert assay is achievement of a rapid diagnosis at a point of care and additional information about drug resistance, rather than an additional yield. An Indian study [35] included pulmonary ( n = 384) and extrapulmonary ( n = 761) samples. Among the latter, the sensitivity of the Gene Xpert assay was 88% and its specificity was 91%.…”
Section: Newer Diagnostic Modalitiesmentioning
confidence: 99%
“…Furthermore, Singh et al, 2016, demonstrated a sensitivity of 100% and specificity of 100% for pulmonary samples by using GeneXpert assay. In addition, Agrawal et al, 2016, reported that the sensitivity and specificity of GeneXpert in sputum were 100% and 90% that is compatible with the study of Sharma et al, 2015who found a sensitivity of 96.9% and a specificity of 99.8%.…”
Section: Resultsmentioning
confidence: 99%